Upper Palaeolithic ritualistic cannibalism at Gough's Cave (Somerset, UK): The human remains from head to toe. Issue 82 (May 2015) - Bello, Silvia M.; Saladié, Palmira; Cáceres, Isabel; Rodríguez-Hidalgo, Antonio; Parfitt, Simon A.
Abstract: A recurring theme of late Upper Palaeolithic Magdalenian human bone assemblages is the remarkable rarity of primary burials and the common occurrence of highly-fragmentary human remains mixed with occupation waste at many sites. One of the most extensive Magdalenian human bone assemblages comes from Gough's Cave, a sizeable limestone cave set in Cheddar Gorge (Somerset), UK. After its discovery in the 1880s, the site was developed as a show cave and largely emptied of sediment, at times with minimal archaeological supervision. Some of the last surviving remnants of sediment within the cave were excavated between 1986 and 1992. The excavations uncovered intensively-processed human bones intermingled with abundant butchered large mammal remains and a diverse range of flint, bone, antler, and ivory artefacts. New ultrafiltrated radiocarbon determinations demonstrate that the Upper Palaeolithic human remains were deposited over a very short period of time, possibly during a series of seasonal occupations, about 14, 700 years BP (before present). The human remains have been the subject of several taphonomic studies, culminating in a detailed reanalysis of the cranial remains that showed they had been carefully modified to make skull-cups. Our present analysis of the postcrania has identified a far greater degree of human modification than recorded in earlier studies. We identify extensive evidence for defleshing, disarticulation, chewing, crushing of spongy bone, and the cracking of bones to extract marrow. The presence of human tooth marks on many of the postcranial bones provides incontrovertible evidence for cannibalism. In a wider context, the treatment of the human corpses and the manufacture and use of skull-cups at Gough Cave have parallels with other Magdalenian sites in central and western Europe. This suggests that cannibalism during the Magdalenian was part of a customary mortuary practice that combined intensive processing and consumption of the bodies with ritual use of skull-cups.